Comparison Analysis of Junior High School Science Textbooks in Indonesia and Singapore View from Nature of Science (NoS) Aspects - Sumi Sumarni; Sri Haryati; Eli Trisnowati; Siswanto Siswanto; Moch. Malik Al Firdaus; Suwito Singgih (Postgraduate, University of Mataram, 2022)
Scientific literacy can prepare quality human resources who can develop the ability to think logically and creatively, solve problems, be critical, master technology and be adaptive in the face of change and face the times. A vital component to improving students' scientific literacy is understanding the Nature of Science (NoS), which must be emphasized in science learning. The purpose of this study is to obtain a comparison of content and explain aspects of NoS in science textbooks in Indonesia and Singapore. The research approach used is descriptive qualitative with content analysis design. This research focuses on science books for Junior High School Class IX Semester 1 Curriculum 2013 Revised Edition 2018, Integrated Science Books for Junior High School Class IX Curriculum 2013 Revised Edition 2018, and Lower Secondary Science Matters Textbook Volume B 2nd Edition 2013. The data collection techniques are by reviewing documents with non-test instruments in the form of observation guidelines for assessing textbooks based on the NoS aspect developed by Abd-El-Khalick et al., (2008). The data analysis technique uses the fixed comparison method by Moleong (2014). The results obtained are that the textbooks from the two countries have represented several relevant aspects of NoS. Still, the theoretically-driven elements have not been found in the three books, and the existing components have not been well described. Science textbooks in Singapore get a higher score than science textbooks in Indonesia. Still, the availability of the NoS aspect of science textbooks in Indonesia is more than that of science textbooks in Singapore.